Penyelenggaraan dan Peranan Bantuan Hukum di Indonesia - Solikin; Adi Wijaya; Heri Budianto; Slamet Nurjoyo (LPPM STIH Awang Long, 2019)
This study aims to analyze national legal arrangements regarding legal aid, as well as to analyze the provision of legal aid to citizens. This research is a normative study, using a statutory approach, a conceptual approach, and a historical approach, the data used are primary and secondary legal materials, all data collected were analyzed qualitatively. The results showed that the Law on Legal Aid regulates the meaning of Legal Aid, Beneficiary Legal Aid, Legal Aid Providers, rights and obligations of Legal Aid Recipients, terms and procedures for legal aid applications, funding, prohibitions, and criminal provisions. The Law on Legal Aid exists because the right to legal aid has been universally accepted as guaranteed in the International Covenant on Civil and Political Rights (ICCPR). Articles 16 and 26 of the ICCPR guarantee that all people have the right to legal protection and must be protected from all forms of discrimination. The provision of legal aid to citizens is an effort to fulfill and at the same time implement a rule of law that recognizes and protects and guarantees the human rights of citizens regarding the need for access to justice and equality before the law.